2006
DOI: 10.1080/02688690601012175
|View full text |Cite
|
Sign up to set email alerts
|

Operative and hardware complications of deep brain stimulation for movement disorders

Abstract: The objective of this investigation was to present the operative and hardware complications encountered during follow-up of patients with in situ deep brain stimulators. The study took the form of a retrospective chart review on a series of consecutive patients who were treated successfully with insertion of deep brain stimulators at a single centre by a single surgeon between 1999 and 2005. During the study period, a total of 60 patients underwent 96 procedures for implantation of unilateral or bilateral DBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 19 publications
1
29
1
1
Order By: Relevance
“…Although Lyons et al [5] noted hardware complications related to DBS placement in 26.2% of patients, with 10% involving the extension wire requiring additional surgery, they did not note any incidents of wire tethering, perhaps in part because this series predated the availability of dual-channel IPGs. Similarly, this complication was not noted in the series of 60 patients (96 procedures) reported by Paluzzi et al [6] , but it is not noted whether any of their bilateral patients had dual-channel IPGs (and dual-unilateral extension wires) or two single-channel devices. Voges et al [2] noted extension wire or extension connector-related circumscribed discomfort in 12 of 180 DBS patients (6.7%).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although Lyons et al [5] noted hardware complications related to DBS placement in 26.2% of patients, with 10% involving the extension wire requiring additional surgery, they did not note any incidents of wire tethering, perhaps in part because this series predated the availability of dual-channel IPGs. Similarly, this complication was not noted in the series of 60 patients (96 procedures) reported by Paluzzi et al [6] , but it is not noted whether any of their bilateral patients had dual-channel IPGs (and dual-unilateral extension wires) or two single-channel devices. Voges et al [2] noted extension wire or extension connector-related circumscribed discomfort in 12 of 180 DBS patients (6.7%).…”
Section: Discussionmentioning
confidence: 71%
“…Extension wire complications represent a subset of deep brain stimulation (DBS) hardware-related problems that have been infrequently reported [1][2][3][4][5][6] . In this report we specifically address the presentation and treatment of wire tethering or 'bowstringing' (a term that has made it into the DBS lexicon but which has never appeared in published reports).…”
Section: Introductionmentioning
confidence: 99%
“…Others have found increased rates of mortality (< 0.4%), intracranial hemorrhage (< 2%), and infections (< 5%). 19,25,33 Adverse effects such as hyperkinesia were typically resolved with optimal resetting of the stimulation parameters. For 3 patients, hyperkinesia persisted despite adjustment: 2 with STN stimulation and 1 with GPi stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The calculated incidence of complications associated with laparoscopic bariatric surgery, obtained from the case series, 4,8,10,17,28,38,44,45,52,74,77,82,83,91,120 is summarized in Table 1; complications associated with DBS studies are shown in Table 2. 6,7,9,12,16,20,26,27,31,37,39,47,[55][56][57][58][59][60][61]64,[67][68][69]71,78,80,81,84,[86][87][88][89][96][97]…”
Section: Resultsmentioning
confidence: 99%
“…63 Inclusion of elderly patients with movement disorders may contribute to the complication rate associated with DBS. 13,34,81 Thus, DBS complications among younger patients who are eligible for bariatric surgery would be expected to occur less frequently. If DBS for obesity is offered to elderly patients with morbid obesity, the complication rates observed in this study would no longer be an overestimate.…”
mentioning
confidence: 99%